ANALISIS USAHATANI KAKAO ORGANIK STUDI KASUS KELOMPOK TANI SIDO DADI DUSUN GUMAWANG DESA PUTAT KECAMATAN PATUK KABUPATEN GUNUNGKIDUL DAERAH ISTIMEWA YOGYAKARTA - Selvina Helmalia Arista Adi; Nurlina Harli (Fakultas Pertanian, Universitas Janabadra, 2023)
This study aims to determine the income of organic cocoa farming in the Sidodadi farmer group. The research was conducted at the “Sidodadi” Organic Cocoa Farmers Group, Gumawang, Putat, Patuk District, Gunung Kidul. Data collection was carried out during April 2023. Data sources are in the form of primary data and secondary data. Primary data were obtained from observations and also asked questions using a questionnaire to the respondents. Respondents in this study were all members of the